Hubungan Pengetahuan Dengan Sikap Ibu Hamil Tentang Manfaat Rebusan Air Jahe Dalam Mengurangi Mual Muntah Pada Ibu Hamil Trimester I - Ester Pakpahan; Elda Naila Rizki (STIKES Columbia Asia Medan, 2025)
Nausea and vomiting during the first trimester of pregnancy are common physiological symptoms that may interfere with maternal comfort and nutritional intake. One widely accepted non-pharmacological therapy to reduce these symptoms is ginger decoction, due to its antinausea properties derived from active compounds such as gingerol and shogaol. This study aims to determine the relationship between pregnant women's level of knowledge and their attitudes toward the use of ginger decoction to alleviate nausea and vomiting in the first trimester. This research employed a quantitative method with a descriptive-analytic design. The population included all first-trimester pregnant women visiting Pratama Madina Clinic during January–February 2024, totaling 47 respondents selected using total sampling. Data collection used a structured questionnaire, and the data were analyzed using univariate and bivariate techniques, with the Chi-square test applied. The results showed that 75% of respondents had good knowledge and demonstrated a positive attitude toward using ginger decoction. The Chi-square analysis revealed a significant relationship between knowledge and attitude (p = 0.000). The study concludes that knowledge level influences pregnant women's attitudes toward herbal therapy, and ginger decoction is well-accepted as a non-pharmacological option to reduce pregnancy-related nausea and vomiting. Further health education is recommended to enhance awareness of safe and effective natural therapies for pregnant women.